Effect of Cost Cutting Strategy on Performance of Star Rated Hotels in Nairobi County - Kiprop, Victor Kibet; Kiplagat, Nehemiah; Kamau, Geoffrey (The International Journal of Business Management and Technology, 2023)
While the hospitality industry makes a great contribution to the economic development of a country, many hotels encounter organizational challenges associated with poor cost cutting. Such result, huge losses and sometimes closure of business. It is on this basis that this study sought to investigate the effect of cost cutting strategy on the performance of star rated hotels in Nairobi County, Kenya. The study was guided by lean management theory. The target population of the study was 61 general managers of the 61 star rated hotels in Nairobi County. The study adopted census approach to incorporate all the 61 managers involved in the study. The study was quantitative in nature and adopted a correlational research design, structured questionnaire was used collect primary data and data was analyzed using a statistical package for social sciences where descriptive statistics; mean and standard deviation. Inferential statistics involved the use of Pearson’s Product Moment correlation and multiple regression models to determine the nature of the relationship between the variables. The findings of the study were presented in table form. The study concluded that cost cutting strategy has no statistically significant effect on performance of star rated hotels in Nairobi County (r=0.924, p=0.000). The study recommends that the hotels should consider sourcing supplies from cost conscious suppliers. They can adopt more cost-effective methods of production and service delivery. Lastly, the hotels should embark on prudent purchasing to reduce wastages and unnecessary cost
Keywords: Cost Cutting Strategy; Performance